2019
DOI: 10.3389/fendo.2018.00775
|View full text |Cite
|
Sign up to set email alerts
|

Tetrac Delayed the Onset of Ocular Melanoma in an Orthotopic Mouse Model

Abstract: Ocular melanoma research, the most common primary intraocular malignancy in adults, is hindered by limited in vivo models. In a series of experiments using melanoma cells injected intraocularly into mouse eyes, we developed a model for ocular melanoma. Inoculation of 5 × 105 B16F10 cells led to rapid tumor growth, extensive lung metastasis, and limited animal survival, while injection of 102 cells was sufficient for intraocular tumors to grow with extended survival. In order to improve tumor visualization, 102… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The integrin αvβ3-mediated TH actions that are relevant to cancer biology can be regulated by the 3,3′,5,5′-tetraiodothyroacetic acid—a deaminated form of T4 known as tetrac—and its nanoparticulate analog—known as nano-diamino-tetrac (NDAT) or tetrac-NP [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Tetrac is a monocarboxylic acid carrying four iodo substituents at positions 3, 3′, 5 and 5′.…”
Section: Molecular Aspects Of the Actions Of Thmentioning
confidence: 99%
“…The integrin αvβ3-mediated TH actions that are relevant to cancer biology can be regulated by the 3,3′,5,5′-tetraiodothyroacetic acid—a deaminated form of T4 known as tetrac—and its nanoparticulate analog—known as nano-diamino-tetrac (NDAT) or tetrac-NP [ 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Tetrac is a monocarboxylic acid carrying four iodo substituents at positions 3, 3′, 5 and 5′.…”
Section: Molecular Aspects Of the Actions Of Thmentioning
confidence: 99%
“…Overexpression and activation of the protein renders tumor cells susceptible to actions of T4 to stimulate proliferation, to support cancer cell defense pathways such as anti-apoptosis (7) and radioresistance (8), and to enhance cancer-related angiogenesis (2,3,9,10). Preclinical studies have shown a variety of tumor cells to proliferate in response to physiological concentrations of T4 (11)(12)(13)(14). A derivative of T4, tetraiodothyroacetic acid (tetrac), blocks actions of T4 on tumor cell avb3 (3).…”
Section: Introductionmentioning
confidence: 99%
“…Given the promising capacity of luciferase-expressing melanoma cells to grow and to be quantified after grafting in zebrafish eyes, we decided to extend this assay to a well-established murine melanoma model suitable for investigating the mechanisms responsible for uveal melanoma liver tropism [ 30 , 31 , 32 ], immunologic and angiogenic aspects [ 33 ], and drug response [ 34 , 35 , 36 , 37 ]. On this basis, B16-LS9-luc + cells were injected in the zebrafish embryo eye, grafts were analyzed at t 0 and t 4 , and immunohistochemical analysis of cell grafts showed that tumor cells proliferate, as already observed for B16-BL6 tumors ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%